On the use of the Internet to collect earthquake information - Paul S. Earle; Rémy Bossu (Annals of Geophysics, 2011)
As geophysicists, we find it difficult to imagine our daily professional and personal lives without the Internet. Emails have been the mainstay of scientific communication since the 1980’s and websites, since their inception in the 1990’s, have grown to represent the heart of public information dissemination. Now, scientific data flow in real-time around the world through custom protocols, portals, and web services, and the advent of social media services such as Facebook and Twitter offer both a new mechanism to communicate ideas and a potential resource for collecting data. [...]